Implementasi Pendidikan Kewarganegaraan dengan Sikap Toleransi Peserta Didik di Sekolah Dasar - Artha Viola (Indo Publishing, 2026)
The introduction of citizenship education is needed to foster tolerance in students from an early age. Citizenship education aims to develop the moral qualities necessary to instill a sense of love for the country, foster national pride, foster a high sense of tolerance, and develop a sense of national identity that is in line with Pancasila, philosophy, world view and state ideology. One of the conditions for upholding Pancasila values ​​and fostering positive relations among Indonesian society is tolerance. Knowledge about how important it is to teach tolerance to elementary school students is the benefit of this article. The purpose of this article is to show how to use the tolerance-encouraging mindset you have developed through Citizenship Education in real-world situations. This article uses a qualitative methodology, collecting and evaluating data from a literature review. Students will learn how to develop a positive attitude of tolerance as a result of this essay.